PERILAKU FINANSIAL MAHASISWA PENDIDIKAN AKUNTANSI: PERAN LITERASI KEUANGAN DAN GAYA HIDUP - Dzidni, Dzilma Arij; Chaerudin, Khanum Hanurawati; Yuniar, Nooreha Fitria; Saputri, Sheila Stefanie; Susilowati, Nurdian (Buletin Literasi Budaya Sekolah, 2025)
The objective of this research is to analyze the impact of financial literacy and lifestyle on students’ financial behavior. This study is motivated by a significant gap between access to financial services and the understanding of financial management—especially among university students transitioning into financial independence. Despite the easy access to digital financial tools, many students exhibit weak financial habits, often influenced by low financial literacy or by social pressures that encourage consumerist behavior. This study applies a quantitative causal-comparative approach involving 100 active undergraduate students as respondents, filtered by purposive sampling with criteria of having managed personal finances independently. A structured questionnaire using a Likert scale format was used to gather data with items designed to assess aspects of financial literacy, personal lifestyle, and financial behavior. The data were analyzed using multiple linear regression with SPSS version 25. The findings show that financial literacy has a significantly positive effect on students’ financial behavior (t = 5.821, p = 0.000), whereas lifestyle shows no significant partial effect (t = 0.157, p = 0.875). However, when tested simultaneously, both variables significantly contribute to the model with R² = 0.262 and showing that financial literacy and lifestyle together account for 26% of the variation in financial behavior. These results reinforce the importance of financial literacy as a key determinant of healthy financial behavior and emphasize the need for practical and behavior-oriented financial education programs. The study also suggests further refinement of instruments measuring lifestyle to better capture social dynamics influencing financial decisions among students.